Promoting gender equity in marine protected areas: A self-assessment tool - Bonilla Anariba, Sara; Sanders, Arie; Canty, Steven (Elsevier, 2025)
There is an increasing role of marine protected areas (MPAs) to be the dominant form of marine resource management to protect biodiversity, promote livelihoods, and build food security as part of the sustainable development agenda. However, the effective and equitable achievement of these goals requires understanding women's use, access to, and dependence on marine resources and integrating their knowledge and experiences. Currently, there is inherent gender blindness in the establishment and management of MPAs, which is likely to be confounded as existing MPAs are expanded and new areas are designated. Here we present a self-assessment tool for gender sensitivity within MPA management interventions. The tool is centered on the Feminist Political Ecology approach, which central argument is that different genders experience the environment differently due to their divergent social and cultural roles. The tool evaluates gender sensitivity of management interventions using a total of 15 questions evenly distributed between five themes: Gender power roles; Gendered uses and values; Gendered knowledge, interests, and priorities; Gender-responsiveness management design; and Gender-inclusiveness management design. Responses to all questions are evaluated on a gender awareness scale; 1 = incipient gender awareness; 2 = becoming gender aware; 3 = gender aware; and 4 = gender transformative. The scores for each theme and across the entire assessment are averaged to identify where actions need to be focused. Understanding the power dynamics associated with the access to and control of marine resources will facilitate greater inclusion of women in marine resource management and contribute to the sustainable development agenda.